Influence of shape and heat release of thermal passenger manikins on the performance of displacement ventilation in a train compartment. Issue 6 (July 2020) - Schmeling, Daniel; Bosbach, Johannes
The influence of sensible heat release on the performance of displacement ventilation was studied in a generic laboratory representing the lower cabin of the German Aerospace Center (DLR)'s Next Generation Train. Tests at variable mean cabin temperatures were conducted with human subjects, thermal manikins and heating mats at different but constant heat release rates. Moreover, tests with thermal manikins and an adaptive heat release rate were performed. Flow fields, surface temperature distributions as well as local temperatures and velocities were evaluated. The study revealed that the shape of the heat sources is negligible if only global quantities, such as the global enthalpy flux or the heat removal efficiency, are evaluated. The latter was found to be independent of the amount of released heat. However, it strongly reacts to the choice of probe positions used for the mean cabin temperature. Regarding the comfort-relevant flow parameters, both the shape and the heat release rate are highly relevant to temperature stratifications and flow fields in the passenger zone. The manikins with adaptive heat release proved to be a major improvement in terms of realistic simulation of the human metabolism for investigations regarding the performance of ventilation systems. However, the determination of the mean cabin temperature receives increased relevance as it is prone to limit the closeness to reality.